(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Many villages in the Jizzakh region are located on the territory of ecotourism zones and nature reserves. The village of Peshagar, Zominsky district, is one of such villages. This village is a place with high potential for ecotourism with its valleys, natural caves, mountain forest landscapes and clean air.